Chitosan-induced biotic stress tolerance and crosstalk with phytohormones, antioxidants, and other signalling molecules - Mukarram, Mohammad; Ali, Jamin; Dadkhah-Aghdash, Hamed; Kurjak, Daniel; Kačík, František; Ďurkovič, Jaroslav (Frontiers in Plant Science, 2023)
Several polysaccharides augment plant growth and productivity and galvanise defence against pathogens. Such elicitors have ecological superiority over traditional growth regulators, considering their amplified biocompatibility, biodegradability, bioactivity, non-toxicity, ubiquity, and inexpensiveness. Chitosan is a chitin-derived polysaccharide that has recently been spotlighted among plant scientists. Chitosan supports plant growth and development and protects against microbial entities such as fungi, bacteria, viruses, nematodes, and insects. In this review, we discuss the current knowledge of chitosan's antimicrobial and insecticidal potential with recent updates. These effects are further explored with the possibilities of chitosan's active correspondence with phytohormones such as jasmonic acid (JA), salicylic acid (SA), indole acetic acid (IAA), abscisic acid (ABA), and gibberellic acid (GA). The stressinduced redox shift in cellular organelles could be substantiated by the intricate participation of chitosan with reactive oxygen species (ROS) and antioxidants metabolism, including hydrogen peroxide (H2O2), superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD). Furthermore, we propose how chitosan could be intertwined with cellular signalling through Ca 2+ , ROS, nitric oxide (NO), TFs, and defensive gene activation.